L’ombra del Cigno Nero sui rapporti negoziali: il riequilibrio contrattuale nelle locazioni ad uso commerciale a seguito delle restrizioni per il CoViD-19 (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The Black Swan shadow of CoViD-19 looms over contracts, undermining traditional remedies for asset default. The relationship between landlord and tenant is altered by the restrictive measures against the pandemic, however, are required by contract to pay the rent. Specific rules have been introduced for some types of contracts in order to exempt from contractual liability entrepreneurs, but they are not general. The issue of “contingency law” is therefore highly topical: the theme of the revision of the contract and the execution of the contract in good faith and in compliance with the duty of solidarity ex art. 3 of the Constitution necessarily returns.
Keywords: CoViD-19; pandemic emergency; lease; rental fee; duty of solidarity